Management of amlodipine-induced gingival enlargement: Series of three cases - Srivastava Amit; Kundu Debabrata; Bandyopadhyay Prasanta; Pal Asit (Wolters Kluwer Medknow Publications, 2010)
Gingival enlargement is one of the side effects associated with certain drugs. Amlodipine, a calcium channel blocker, used as antihypertensive drug has been found associated with gingival hyperplasia. This case series presents diagnosis and management of amlodipine-induced gingival hyperplasia. Amlodipine-induced gingival enlargement was diagnosed and managed by thorough scaling and root planning. Drug substitution and surgical intervention was performed in first two cases. The pathogenesis of gingival enlargement is uncertain and the treatment is still largely limited to the maintenance of an improved level of oral hygiene and surgical removal of the overgrown tissue. Several factors may influence the relationship between the drugs and gingival tissues as discussed by Seymour et al. Meticulous oral hygiene maintenance, switchover to alternative drug, professional scaling and root planning and surgical excision of enlarged gingival tissue may help overcome the effect of these drugs.